Risk assessment of biological exposure in health workers of west walenrang health center - Nur Al Mughnia; Lusia Salmawati; Musjaya M Guli; Vidyanto Vidyanto; Sumarni Sumarni (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2026)
Introduction: Biological hazards remain a primary occupational health concern for healthcare workers, particularly in primary healthcare centers where frequent contact with patients, biological specimens, and infectious medical waste occurs. Limited infrastructure and suboptimal occupational safety and health (OSH) implementation further increase the risk of biological exposure among healthcare workers at the primary care level. Research Methodology: This study employed a mixed-methods, sequential explanatory design at the West Walenrang Health Center. Quantitative data were collected through field observations and structured questionnaires administered to all 48 healthcare workers, using total sampling. Biological risks were identified and assessed using the Hazard Identification, Risk Assessment, and Determining Control (HIRADC) method with a risk matrix. Qualitative data were obtained through in-depth interviews with selected healthcare workers from high-risk units to explore contextual factors influencing biological risk exposure and control practices. Results: The findings indicated that biological hazards were the most dominant occupational risks. High-risk exposures were primarily associated with contact with blood and body fluids, needlestick and sharps injuries, and improper management of infectious medical waste, each scoring 12 on the HIRADC risk matrix. Moderate risks were identified in relation to direct contact with infectious patients and aerosol-generating medical procedures. Existing control measures were largely limited to personal protective equipment and administrative controls, while higher-level controls, such as engineering interventions, were insufficient. Qualitative findings supported these results, highlighting inconsistent use of protective equipment, inadequate waste management, limited training, and weak supervision. Conclusion: Biological risk management at the primary healthcare level remains inadequate. It is recommended that comprehensive HIRADC implementation, improved medical waste management systems, regular occupational safety training, and the integration of higher-level control measures be strengthened to reduce biological exposure among healthcare workers effectively.